3.9k views
5 votes
Simplify the expression.

Simplify the expression.-example-1
User Logaretm
by
6.4k points

1 Answer

6 votes
Hi there! The answer is 30.

We need to use PEMDAS to simplify.
P = parenthesis
E = Exponents
M = Multiply
D = Dividing
A = Adding
S = Subtracting


10(4 * 10 / ( {6}^(2) - {4}^(2) ) + 1)
First find the exponents inside the middlest parenthesis.


10(4 * 10 / (36 - 16) + 1)
Now add inside the parenthesis.


10(4 * 10 / 20 + 1)
Multiply inside the parenthesis that are left.


10(40 / 20 + 1)
Divide inside the parenthesis


10(2 + 1)
Add inside the parenthesis.


10(3)
Multiply.


30
~ Hope this helps you!
User Hansika
by
5.8k points